The Effect of Axial Displacement of Magnets in Piezoelectric Energy Harvester - Wah Thong, Li; Jing Bong, Yu; Leong Kok, Swee; Ramlan, Roszaidi (International Journal of Engineering and Technology, 2018)
The utilization of vibration energy harvesters as a substitute to batteries in wireless sensors has shown prominent interest in the literature. Various approaches have been adapted in the energy harvesters to competently harvest vibrational energy over a wider spectrum of frequencies with optimize power output.Â Â A typical bistable piezoelectric energy harvester, where the influence of magnetic field is induced into a linear piezoelectric cantilever, is designed and analyzed in this paper. The exploitations of the magnetic force specifically creates nonlinear response and bistability in the energy harvester that extends the operational frequency spectrum for optimize performance.Â Further analysis on the effects of axial spacing displacement between two repulsive magnets of the harvester, in terms of x-axis (horizontal) and z-axis (vertical) on its natural resonant frequency and performance based on the frequency response curve are investigated for realizing optimal power output. Experimental results show that by selecting the optimal axial spacing displacement, the vibration energy harvester can be designed to produce maximized output power in an improved broadband of frequency spectrum.Â Â